Investigation of the fusion rate of lumbar spondylolysis in junior and senior high school students in our hospital (first report): -Treatment with a semi-rigid corset for unilateral cases - Nakamura, Toshifumi; Terakado, Atsushi; Okachi, Koshiro; Mitsuhashi, Ayano; Ohtori, Seiji (Journal of Spine Research, 2023)
The rate of bone fusion in lumbar spondylolysis during the growth period changes depending on the disease stage (morphology) of the separation, and the corset used. In this study, the subjects were limited to junior high school and high school students with unilateral lumbar spondylolysis, all of whom used a semi-rigid corset, and the rate of bone fusion according to disease stage (morphology) classification was investigated.A total of 127 subjects/134 sites, with unilateral lumbar spondylolysis and who underwent treatment with a semi-rigid corset were included from among the junior and senior high school students who visited our hospital between June 2015 and November 2019. Bone fusion was determined by CT scan after the patients' back pain on extension disappeared.The fusion rate was 100% (type Ia−) in the very early stage, 95.2% (type Ia) and 87.5% (type Ib) in the early stage, 40% (type II) in the advanced stage, and 0% (type III) in the terminal stage.It is possible to obtain sufficient bone fusion with a semi-rigid corset for lumbar spondylolysis in the growth period in junior high school and high school students, unilateral cases, and very early-to-early stages.